The velocity of money - Garvy, George; Blyn, Martin R.; Federal Reserve Bank of New York. (New York : Federal Reserve Bank of New York, 1969)
The book examines the role of money in the economy and analyzes the relationship of income to the stock of money-the velocity of money.
Bibliographical footnotes.
usc 14/09/17
Loans
Keywords: Bank deposits; Money; Circular velocity of money